Addressing the humanitarian crisis in Afghanistan through $10 billion Afghani assets: what are the challenges and opportunities at hand? - Mohammad Yasir Essar; Henry Ashworth; Arash Nemat (BMC, 2022)
Abstract Background The current humanitarian crisis in Afghanistan started after the US and international allies' withdrawal. This has put the country in a dire situation as the globalized infrastructure supporting Afghanistan came to halt. Moreover, 10 billion USD of Afghanistan's assets were frozen by the U.S and other international organizations after the Taliban takeover. This further exacerbated the humanitarian crisis and quickened the economic collapse in Afghanistan. These assets should be freed to support the people of Afghanistan. Main body In order to address this situation, international oversight is needed to allow these funds to be returned and used by the Central Bank of Afghanistan without misappropriation by the Taliban. We suggest a number of short term interventions and long term considerations to improve the situation in Afghanistan with the $10 billion in frozen assets. In the short term, economic stability and the hunger crisis should be addressed by funding international organizations such as the World Food Program and national Afghani NGOs. In the long term funds should be used to build back the economy, build healthcare infrastructure, and support the development of women and children. Conclusion At this juncture, the world and international organizations have a moral and ethical responsibility to ensure the 10 billion in funds go to the owners, the people of Afghanistan. With oversight and fund distribution to the right partners, progress can be made by providing support in security, healthcare, education and food resources. This calls for action to deliver $10 billion of assets to the Afghan people in a transparent manner, avoiding further tension and disasters in the country.